The Reasons for Late Initiation of Antenatal Care and Self-care Experiences without Receiving Antenatal Care by Pregnant Women in Yala Province: Qualitative Descriptive Research: Maneeratsami Pattanasombutsook - Pattanasombutsook, Maneeratsami; Siriphan, Siriphan; Chantarasiriput, Boonkanas; Bunlap, Paseena; Niha, Soraya; Mama, Juthamas; Korwiwatanakarn, Suwannee (Princess of Naradhiwas University Journal, 2024)
The purpose of this qualitative descriptive study was to investigate the causes of delayed antenatal care initiation as well as the experiences of self-care when antenatal care was not received. The 18 samples were selected using the purposive sampling technique. Informants were pregnant mothers who received care at one of the hospitals in Yala province, had received antenatal care for the first time after reaching the gestational age of 12 weeks. The depth interview questionnaire was the opened semi-structured questionnaire was validated the contents by three experts. Data transcription was conducted word-by-word. Content analysis technique was applied in data analysis. Results found that there were eight primary reasons for late initiation of antenatal care, which included: 1) ignorance about becoming pregnant; 2) uncertainty about becoming pregnant; 3) pregnancy as a normal situation for self-care; 4) ignorance of the benefits of antenatal care; 5) uncertainty about the appropriate timing for antenatal care; 6) finding it inconvenient to obtain antenatal care due to hyperemesis gravidarum, financial burdens, a long distance from home to healthcare services, or a desire to travel with one's spouse; 7) avoidance antenatal care; and 8) antenatal care services weren't appropriate for their needs. Pregnant women who experienced self-care without receiving antenatal care identified two key aspects :1) Continue with the same level of self-care; 2) Try to increase self-care. There are numerous complex direct and indirect factors that contribute to the late initiation of antenatal care. Therefore, it is crucial to carefully consider the causes and related aspects when preventing and modifying issues related to pregnant women starting late initiation of antenatal care. Additionally, it is important to encourage pregnant women to take care of themselves properly.